Urban greenspace and cardiovascular disease comorbidity at breast cancer diagnosis in the US: regional, racial/ethnic, and socioeconomic variations among older women - Jean C. Bikomeye; Emily L. McGinley; Yuhong Zhou; Sergey Tarima; Jamila L. Kwarteng; Andreas M. Beyer; Tina W.F. Yen; Aaron N. Winn; Kirsten M.M. Beyer (Cancer Survivorship Research & Care)
Objective To investigate the association between urban greenspace and cardiovascular disease (CVD) comorbidity at breast cancer (BC) diagnosis among older women, and explore regional, racial/ethnic, and socioeconomic differences.Study design A cross-sectional analysis of population-based registry data.Methods Using the Surveillance, Epidemiology, and End Results (SEER)-Medicare linked database, data on women aged 66-90 diagnosed with BC (2010-2017) were analyzed. A tract-level measure of tree canopy cover was derived from the National Landcover Database (2011) and linked to SEER-Medicare records. Logistic regression models assessed the probability of CVD comorbidity based on state-specific percent tree canopy quartiles, adjusting for covariates.Results Out of 116,660 women, 74.7% (n = 87,152) had CVD comorbidity at BC diagnosis. Overall, women residing in areas with higher percent tree canopy cover had a lower likelihood of CVD comorbidity compared to those in the lowest canopy areas, with Adjusted Odds Ratio (AOR) and 95% confidence interval (CI) of 0.89 (0.84-0.94). Racial/ethnic, socioeconomic status (SES), and regional variations were noted. Adjusted effects of greenspace were significant only for NHW women; AOR (95%CI) = 0.78 (0.71-0.86). Women in the highest tree canopy quartile in California, New Jersey, and New Mexico had lower odds of comorbid CVD, with AORs (95% CI) of 0.80 (0.72-0.88), 0.77 (0.71-0.84), and 0.46 (0.34-0.63) respectively. Adjusted results for New York, Massachusetts, and Kentucky showed adverse harmful effects, while adjusted results for all other SEER states were not statistically significant. Both dual enrollment eligible and non-eligible women had benefits from greenspace, but greater benefits were observed in dual enrollment eligible women; AOR (95% CI) =  0.64 (0.48-0.86) versus 0.76 (0.69-0.84) for non-eligible women.Conclusions Overall, urban greenspace is associated with a lower risk of CVD comorbidity among older women with BC, and variations exist by region, race/ethnicity, and SES. Our findings underscore the role of greenspace in mitigating Cardio-Oncology disparities. Further research is needed to better understand factors contributing to observed differences across SEER regions and racial/ethnic subgroups. A better understanding of interactions among greenspace, other environmental factors, and individual lifestyle factors will help improve CVD outcomes among women with BC.